To study the influences of the compensation, work environment and motivation on employee satisfaction among industrial trainees - Sam, Li Xing (2024)
This study investigates the effects of motivation, work environment, and compensation on employee happiness in industrial trainees. Dependent variables include compensation, the environment at work, and motivation; is there a connection between these variables and industrial trainees' employee satisfaction.